Aktualisasi Nilai-nilai Toleransi Beragama di Sekolah Menengah Atas - Miftahul Mufid; Farida Isroani (Medan Resource Center, 2022)
The actualization ??of religious tolerance is a standard of co nsideration consistent concept of humans towards mutual respect of other religions by living together without mixing beliefs. This research uses a qualitative case study approach through observation, interview and documentation. The results of the study show that: the values ??of religious tolerance which are internalized in the subject of Islamic Religious Education at Sekolah Menengah Atas have been well actualized by students and all school members through the realization of school programs that support the internalization of religious tolerance values, namely the movement peace schools and ROHIS religious programs; such as cultural bazaar activities, scripture literacy, visits to places of worship, interfaith dialogue, and religious tolerance KIR competitions. The supporting factor for the actualization of the value of tolerance at senior high school is the goal orientation of each school member, including the principles of wholeness, unity, humanism, and socialism. While the inhibiting factors are based on experience and basic understanding related to religious differences which are influenced by: (1) character and personality, (2) psychological development, (3) parenting pattern, (4) lack of religious teaching, (5) the surrounding environment and culture, and (6) previously established social relations.